Understanding the patient experience of living with notalgia paresthetica: A qualitative interview studyCapsule Summary - Elizabeth D. Bacci, PhD; Brooke M. Currie, MPH; Rozanne Wilson, PhD; Jenny Qian, MS; Catherine Munera, PhD; Kristine Nograles, MD, MSc (Elsevier, 2022)
Background: Notalgia paresthetica (NP) is a chronic sensory neuropathy that causes intense pruritus, typically affecting the upper portion of the back and lasting for months to years. The impacts of pruritus and the full symptom experience are not well documented. Objective: To describe patients' NP symptom experience and the impacts of living with NP-related itch. Methods: Semistructured, one-to-one qualitative telephone interviews were conducted in adults living with NP. The worst itch severity during the previous 24 hours was assessed using an 11-point numerical rating scale. Results: Thirty participants (23 females; aged 41-80 years) completed interviews. Seventeen NP-related symptoms were described, with daily itch being the most common. Participants' itch ranged from severe to very severe (50%) and was experienced for a median of 2.8 years. Most (73%) participants were not receiving treatment for NP at the time of the study. Other reported symptoms included skin pain or sensitivity and secondary symptoms from itching (skin discoloration, lumps or bumps, bleeding or scabbing). NP-related itch was frequently reported to affect mood, interfere with sleep, and disrupt self-care. Limitations: Only English-speaking participants living in the United States were included. Conclusion: This study highlights the patient experience of living with NP and findings reveal that there remains an unmet need for effective therapeutic options to address NP-related itch.